SOLITONS in OPTICAL FIBERS - ABDELALI Hamana (My University, 2024)
The objective of this dissertation is the theoretical and This memorandum aims to study optical fibers and highlight the phenomena accompanying the spread of electromagnetic pulses through them. In its first part, we focused on highlighting the advantages of optical fibers, which made them the most important modern communications systems, including the small loss, which reaches 0.2dB/km for λ = 1550 nm. is an advantage that there is no competitor to in any type of transmission line. As well as the high transmission capacity of 1014 HZ, while in the second part we dealt with studying the propagation of pulses within optical fibers and other nonlinear phenomena such as FWM CPM SPM and numerical methods to solve them using the split-step Fourier method. And using the Matlab program in the simulation.Finally, we presented an example of dark solitons. --------------------------------------------------------------------------------------- تهدف هذه المذكرة إلى دراسة الألياف البصرية و إبراز الظواهر المرافقة لانتشار النبضات الكهرومغناطيسية عبرها حيث ركزنا في جزئها الأول على إبراز مميزات الألياف البصرية والتي جعلت منها أهم نظم الاتصالات الحديثة من بينها الفقد القليل و الذي يصل إلى 0.2 dB/km لـ λ=1550 nm وهي ميزة لا يوجد منافس لها في أي من أنواع خطوط النقل . و كذلك سعة الإرسال العالية Hz1014 بينما تناولنا في الجزء الثاني لدراسة انتشار النبضات داخل الألياف البصرية وما من بشكل ظواهر لاخطية مثل: SPM و XPM و FMWوالطرق العددية لحلها باستعمال طريقة فورييه ذات الخطوة المنقسمة و استعمال برنامج Matlab في المحاكاة. في الأخير عرضنا مثال عن السليتونات الداكنة. -------------------------------------------------------------------------------------- Ce mémoire vise à étudier les fibres optiques et à mettre en évidence les phénomènes accompagnant la propagation des impulsions électromagnétiques à travers elles.Dans la première partie, nous nous sommes concentrés sur la mise en évidence des avantages des fibres optiques, qui en ont fait le système de communication moderne le plus important, notamment la faible perte, qui atteint 0, 2dB/km pour λ= 1550 nm est un avantage sans concurrence dans aucun type de ligne de transmission. Ainsi que la capacité de transmission élevée de 1014HZ,tandis que dans la deuxième partie nous avons traité de l’étude de la propagation des impulsions dans les fibres optiques et d’autres phénomènes non linéaires tels que FWM CPM SPM et des méthodes numériques pour les résoudre en utilisant la méthode de Fourier en étapes divisées et en utilisant le programme Matlab dans la simulation.Enfin, nous avons présenté un exemple de solitons sombres.